Đặc điểm địa chất trũng Kainozoi Cha Cang - Mường Toong - Tự, Đỗ Văn; Dỹ, Nguyễn Địch; Tấn, Nguyễn Trọng; Tân, Mai Thành; Tùng, Văn Đức; Hà, Vũ Văn (Vietnam Journal of Earth Sciences, 2007)
Geological characterictics of Cha Cang - Muong Toong Genozoic depression